Optimization of TMS target engagement: current state and future perspectives - Lioumis, Pantelis; Roine, Timo; Granö, Ida; Aydogan, Dogu Baran; Ukharova, Elena; Souza, Victor H.; Kičić, Dubravko; Ilmoniemi, Risto J.; Makris, Nikos (Frontiers in Neuroscience, 2025)
Neuromodulation is based on the principle that brain stimulation produces plastic changes in cerebral circuitry. Given the intersubject structural and functional variability, neuromodulation has a personalized effect in the brain. Moreover, because of cerebral dominance and interhemispheric functional and structural differences in the same individual, the characterization of specific brain circuitries involved is currently not feasible. This notion is extremely important for neuromodulation treatments applied in neuropsychiatry. Specifically, the efficacy of the neuromodulation treatments is critically dependent on the anatomical precision of the brain target and the circuitry which has been affected by the TMS intervention. Furthermore, for a complete understanding of how the brain behaves under stimulation, the characterization of its neurophysiological response is necessary as well. This goal can be achieved with TMS–EEG guided by current multimodal neuroimaging techniques in real time, namely MRI-based anatomical segmentation and diffusion MRI-based tractographic analysis.